Is there a contextual interference effect for sub-elite alpine ski racers learning complex skills? - Magelssen, Christian; Haugen, Per; Reid, Robert; Gilgien, Matthias (Frontiers in Bioengineering and Biotechnology, 2022)
Scientific understanding of the contextual interference effect stems mainly from studies on unskilled participants learning artificial laboratory tasks. Although one goal of such studies is to extrapolate the findings to include real-world learning situations such as sports, this generalization is not straightforward. This study tested the contextual interference effect with 66 sub-elite, competitive alpine ski racers who learned a new movement pattern−the pumping technique to increase velocity in slalom−by practicing this skill in three different slalom courses over a 3-day training period. The interleaved group practiced all three courses each day in a semi-random order. In contrast, the blocked group practiced only one course each day, which was randomized and counterbalanced across the participants in this group. A retention test was delivered 72 hours after the last practice day. In contrast to our hypothesis, the interleaved group did not display better retention than the blocked group. The interleaved group's performance was also not attenuated during skill learning compared to the blocked group. Our results underscore the importance of conducting motor learning experiments in natural environments to understand the conditions that facilitate learning beyond the laboratory environment.